Development of Communication Skills of Students of Bina Creatif Broadcasting Vocational High School Medan Through Public Speaking Learning - Riendi Riendi (Yayasan Al'Adzkiya Rantauprapat, 2025)
With his public speaking skills, he will be seen as a qualified person. Because Public Speaking is not only needed by those who work as public speakers such as teachers or lecturers. But also by those who have the need to intersect and communicate with many people. If he does not have a good ability to communicate with others, it will certainly interfere with the things that are doneThis research uses a Descriptive Method with a Qualitative approach, because the data to be collected is empirical data, namely facts in the field. The descriptive method in this study aims to describe the condition of the Public Speaking skills of Bina Creatif Medan Broadcasting Vocational School students, the methods and materials used, and describe the development of students' Public Speaking skills at Bina Creatif Medan Broadcasting Vocational SchoolResearchers conducted interview techniques to obtain data from the Development of Communication Skills of Bina Craetive Medan Broadcasting Vocational School Students through Public Speaking Learning. Based on the results of interviews conducted by researchers with Sir Efendi Syahputra, S.Kom M.I.Kom, Sir M. Syuaib Ambarita, S. Pd, Sir Wahyudi Hidayat, S.Kom M.i,Kom (SMK BBC MEDAN) The importance of public speaking skills is very absolute. This ability underlies everyone's success in various fields.